Pengaruh Supervisi Manajerial Dan Motivasi Kepala Sekolah Terhadap Kinerja Guru Produktif SMK Negeri 2 Prabumulih - Yuyun Inda Sari; Nur Ahyani; Missriani, Missriani (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
This research aims to analyze the influence of managerial supervision and principal motivation on the performance of productive teachers at SMK Negeri 2 Prabumulih. The approach used in this research is quantitative with a survey method. Data was obtained by distributing questionnaires to 50 productive teachers at the school. The data analysis technique used is multiple regression to examine the influence of managerial supervision and principal motivation on productive teacher performance. The results of the research show that managerial supervision has a positive and significant influence on productive teacher performance, as does the motivation of the school principal which also has a positive and significant influence. Simultaneously, these two variables make a significant contribution to increasing the performance of productive teachers at SMK Negeri 2 Prabumulih. Based on the results of this research, it is recommended that school principals improve the quality of managerial supervision and motivation of teachers to support the achievement of better performance.